DIVERSIFIKASI PERUSAHAAN DAN MANAJEMEN LABA - Dewi Lupitasari; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
This study examines the association between corporate diversification and earning management.This study making an explicit distinction between operational and geographicdiversification. Based on a sample of 124 mining and banking companies that listed on theIndonesian Stock Exchange in the period 2010-2011, The result of this study indicates thatoperation diversification did not have significant influence to earning management onmining and banking companies. Higher geographic diversification decrease earningmanagement on mining company. The more the banking company has geographicsegments, the higher the company perfoms earning management. Samples were selected bypurposive sampling method and Data were analyzedusing multiple regression analysis model.